Penerapan Teori Graf Pada Jaringan Komputer Dengan Algoritma Kruskal - Fajar Mahardika (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Graph theory a branch of mathematics that studies graphs of a problem that arises. Problems related to graph theory include electricity grid planning, water networks, computer networks and so on. In this graph theory, many of the methods studied include Minimum Spanning Tree (MST). This MST method is used to determine a minimum of a graph.  In this MST there is an algorithm which is a kruskal algorithm. This kruskal algorithm is used to determine the shortest distance or minimum tree of a graph. The author conducted several trials related to the algorithm to be used. The author also conducts literature studies to determine the existing problems. In this study, choosing graph theory on a computer network with the algorithm used is the kruskal algorithm. In this study the authors conducted several stages such as hypotheses, trials and results. The results of this study are graph theory can be applied to computer networks, the number of devices needed can be known and in this experiment the algorithm gives a very maximum total used.